Oncolytic virotherapy – Forging its place in the immunomodulatory paradigm for Multiple Myeloma. (2021) - Cook, Joselle; Acosta-Medina, Aldo A.; Peng, Kah Whye; Lacy, Martha; Russell, Stephen
Highlights: Oncolytic virotherapy (OV) is a highly adaptable and novel immunomodulatory experimental therapeutic for systemic administration in multiple myeloma. OV is proposed to incite an anti-tumor immune response in the immunosuppressive bone marrow microenvironment, a niche for malignant plasma cell survival and immune evasion. A myriad of OV platforms are being evaluated in preclinical and clinical trials. The OVs can be specifically engineered to enhance tumor specificity, attenuate pathogenicity, increase the immunostimulatory effect, can be armed with anti-oncogenic genes, or modified to encode reporter genes. The future of OV in multiple myeloma will lie in effective combination strategy with other immune-based therapies to induce deep responses and long-lasting remissions. These studies are ongoing. Abstract: The treatment focus for multiple myeloma (MM) has recently pivoted towards immune modulating strategies, with T-cell redirection therapies currently at the forefront of drug development. Yet, despite this revolution in treatment, MM remains without a sustainable cure. At the same time, tremendous advancement has been made in recombinant and gene editing techniques for oncolytic viruses (OV), which have increased their tumor specificity, improved safety, and enhanced the oncolytic and immunostimulatory potential. These breakthrough developments in oncolytic virotherapy have opened new avenues for OVs to be used in combination with other immune-based therapies such as checkpoint inhibitors, chimeric antigen receptor T-cells (CAR-T) and bispecific T-cell engagers. In this review, the authors place the spotlight on systemic oncolytic virotherapy as an adaptable immunotherapeutic for MM, highlight the unique mechanism of OVs in activating the immune-suppressive marrow microenvironment, and lastly showcase the OV platforms and the promising combination strategies in the pipeline for MM.